2023
DOI: 10.1038/s41598-023-46738-0
|View full text |Cite
|
Sign up to set email alerts
|

Blink-related EEG activity measures cognitive load during proactive and reactive driving

Emad Alyan,
Stefan Arnau,
Julian Elias Reiser
et al.

Abstract: Assessing drivers’ cognitive load is crucial for driving safety in challenging situations. This research employed the occurrence of drivers’ natural eye blinks as cues in continuously recorded EEG data to assess the cognitive workload while reactive or proactive driving. Twenty-eight participants performed either a lane-keeping task with varying levels of crosswind (reactive) or curve road (proactive). The blink event-related potentials (bERPs) and spectral perturbations (bERSPs) were analyzed to assess cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…We also endeavoured to examine task-specific overt attention allocation across corners of the track. Previous research has found corner navigation to induce higher levels of cognitive processing while driving [ 19 ]. Therefore, fourthly, we hypothesise that that lower-skilled sim racers will have greater attention allocation than high-skilled sim racers, evidenced by longer average and total fixation durations, and a greater number of fixations in corner sectors when unadjusted for corner sector time (H4).…”
Section: Introductionmentioning
confidence: 99%
“…We also endeavoured to examine task-specific overt attention allocation across corners of the track. Previous research has found corner navigation to induce higher levels of cognitive processing while driving [ 19 ]. Therefore, fourthly, we hypothesise that that lower-skilled sim racers will have greater attention allocation than high-skilled sim racers, evidenced by longer average and total fixation durations, and a greater number of fixations in corner sectors when unadjusted for corner sector time (H4).…”
Section: Introductionmentioning
confidence: 99%